Sex trafficking of girls and women : Evidence from Anantapur district, Andhra Pradesh - U. Vindhya
A crucial gap in the trafficking literature from India is the dearth of primary data and micro studies that could be used for vulnerability mapping of the source areas and addressing the identified risk factors. The present paper is a small attempt to contribute to plugging the gap in the context of Andhra Pradesh, identified as a hot spot in the trafficking literature. This paper is based on case studies of 78 women who had been trafficked from their places of origin in Anantapur district in Andhra Pradesh to metropolitan cities across India and who have since returned to their homes. The paper attempted to identify the individual and family circumstances that contribute to the causes of trafficking, to highlight in particular the gendered vulnerabilities that set these women up for trafficking, and to capture the process of the trafficking experience. The findings of the study are located in the dynamic interplay of the social structural context and specificities of the district that contribute to causes of trafficking and the individual circumstances and agency of the women. The case studies reported in this paper are a pointer to the compelling urgency of interventions that will go beyond the forced / voluntary divide in trafficking and sex work.Andhra Pradesh, India, trafficking